BERUDU ANURA DI SUNGAI KEDURANG, BENGKULU SELATAN DAN PUSAT PENDIDIKAN KONSERVASI ALAM BODOGOL, JAWA BARAT - Luthfia Nuraini Rahman; Achmad Farajallah (Media Konservasi, 2012)
This paper aims is to identify and to describe morphological characteristic of tadpoles in Kedurang River, South Bengkulu and Cisuren River, PPKA Bodogol. Visual Encounter Survey along the river method was used to collect the sample of tadpoles. Three species were found in both rivers, namely Bufo melanostictus, Limnonectes sp. and Rhacophorus sp.  Keywords: tadpole, Bufo melanostictus, Limnonectes sp., Rhacophorus sp, Kedurang River, Bodogol.